ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PENJUALAN PADA CV. TRI KENCANA CILEGON-BANTEN - Yulianto, M. Hendra; Djuharni, Darti (Jurnal Akuntansi Kontemporer, 2019)
The purpose of this study is to analyze and evaluate the implementation of accounting information system for purchases and sales in "CV. TRI KENCANA. The research method used a case study method with descriptive analysis. The results show that many accounting information systemsof purchases and sales carried out in this company are still a lot of weakness, including the uneven division of tasks in accordance with the existing organizational structure, there are multiple functions in several division, there are two departments whose authority and duties are the same but in the organizational structure is separated. Besides, the documents used there are still shortcomings related to internal control that must be done. Therefore in this study, several solutions were provided to overcome the problems, namely, improvement of the organizational structure both in terms of naming, division of tasks, and the incorporation of two departments that have the same function, as well as refinement of the documents used